Interleukin-33 regulates the functional state of microglia - Xiong, Tianqing; Wang, Xingyi; Zha, Yiwen; Wang, Yingge (Frontiers in Cellular Neuroscience, 2022)
Microglia, the most prominent resident immune cells, exhibit multiple functional states beyond their immunomodulatory roles. Nonimmune functions such as synaptic reorganization, removal of cellular debris, and deposition of abnormal substances are mediated by phagocytosis of normal or enhanced microglia. Activation or migration of microglia occurs when environmental cues are altered. In response to pathological factors, microglia change into various phenotypes, preventing or exacerbating tissue damage. Interleukin-33 (IL-33) is an important cytokine that regulates innate immunity, and microglia are thought to be its target cells. Here, we outline the role of IL-33 in the expression of microglial functions such as phagocytosis, migration, activation, and inflammatory responses. We focus on microglial properties and diverse functional states in health and disease, including the different effects of IL-33 perturbation on microglia in vivo and in vitro. We also highlight several well-established mechanisms of microglial function mediated by IL-33, which may be initiators and regulators of microglial function and require elucidation and expansion of the underlying mechanisms.